The Future of AI in Arabic Language Education: Adoption, Expectations, and Pedagogical Implications - Raswan, Raswan; Mustar, Mustar; Tamami, Keysa; Isnaini, Yesinta (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
ملخص: فتح دمج الذكاء الاصطناعي (الذكاء الاصطناعي) في تعليم اللغة العربية آفاقا جديدة في طرق التعلم، مما يوفر تخصيصا وكفاءة وإمكانية وصول غير مسبوقة. ومع ذلك، لا يزال اعتماد الذكاء الاصطناعي في هذا المجال يواجه تحديات كبيرة، بما في ذلك استعداد المستخدم، والفعالية التربوية، والفجوات بين توقعات وحقائق تنفيذ التكنولوجيا. تهدف هذه الدراسة إلى دراسة مستوى تبني الذكاء الاصطناعي في تعلم اللغة العربية، وتوقعات المستخدمين من هذه التقنية، والآثار التربوية التي تسببها. استخدمت هذه الدراسة نهجا مختلطا مع استطلاعات كمية للطلاب والمحاضرين في العديد من مؤسسات التعليم العالي والمقابلات المتعمقة لاكتساب رؤى نوعية حول تجربة المستخدم. تم إجراء تحليل البيانات باستخدام الإحصاءات الوصفية والتحليل المواضيعي لتحديد أنماط الاستخدام والفوائد الرئيسية والعقبات التي تواجه تنفيذ الذكاء الاصطناعي. تكشف النتائج الرئيسية أن الذكاء الاصطناعي قد حسن كفاءة التعلم والوصول إلى الموارد الرقمية، ولكن لا يزال لديه قيود في جوانب التفاعل البشري وفهم السياقات اللغوية المعقدة. تؤكد استنتاج هذه الدراسة أن تحسين الذكاء الاصطناعي في تعليم اللغة العربية يتطلب نهجا تربويا أكثر تكيفا بالإضافة إلى زيادة محو الأمية الرقمية بين المستخدمين. تساهم الدراسة من خلال تقديم رؤى متعمقة حول العوامل المؤثرة في اعتماد الذكاء الاصطناعي بالإضافة إلى تقديم توصيات استراتيجية لمطوري التكنولوجيا والمعلمين لإنشاء نظام بيئي تعليمي قائم على الذكاء الاصطناعي أكثر ابتكارا وشمولية. الكلمات المفتاحية: التبني، الذكاء الاصطناعي، الفعالية، تعلم اللغة، علم أصول التدريس. Abstracts: The integration of artificial intelligence (AI) in Arabic language education has opened up new horizons in learning methods, offering unprecedented personalization, efficiency, and accessibility. However, the adoption of AI in this realm still faces major challenges, including user readiness, pedagogical effectiveness, and gaps between expectations and realities of technology implementation. This study aims to examine the level of adoption of AI in Arabic language learning, user expectations of this technology, and the pedagogical implications it causes. This study used a mixed-method approach with quantitative surveys of students and lecturers at several higher education institutions and in-depth interviews to gain qualitative insights into user experience. Data analysis was carried out using descriptive statistics and thematic analysis to identify usage patterns, key benefits, and obstacles faced in AI implementation. Key findings reveal that AI has improved learning efficiency and access to digital resources, but still has limitations in aspects of human interaction and understanding complex language contexts. The conclusion of this study confirms that the optimization of AI in Arabic language education requires a more adaptive pedagogical approach as well as an increase in digital literacy among users. The study contributes by offering in-depth insights into the factors influencing AI adoption as well as providing strategic recommendations for technology developers and educators to create a more innovative and inclusive AI-based learning ecosystem. Keywords: Adoption, Artificial Intelligence, Effectiveness, Language Learning, Pedagogy Abstrak: Integrasi kecerdasan buatan (AI) dalam pendidikan bahasa Arab telah membuka cakrawala baru dalam metode pembelajaran, menawarkan personalisasi, efisiensi, dan aksesibilitas yang belum pernah ada sebelumnya. Namun, adopsi AI dalam ranah ini masih menghadapi tantangan besar, termasuk kesiapan pengguna, efektivitas pedagogis, serta kesenjangan antara ekspektasi dan realitas implementasi teknologi. Penelitian ini bertujuan untuk mengkaji tingkat adopsi AI dalam pembelajaran bahasa Arab, harapan pengguna terhadap teknologi ini, serta implikasi pedagogis yang ditimbulkannya. Studi ini menggunakan pendekatan mixed-method dengan survei kuantitatif terhadap mahasiswa dan dosen di beberapa institusi pendidikan tinggi serta wawancara mendalam untuk memperoleh wawasan kualitatif mengenai pengalaman pengguna. Analisis data dilakukan menggunakan statistik deskriptif dan analisis tematik guna mengidentifikasi pola penggunaan, manfaat utama, serta hambatan yang dihadapi dalam implementasi AI. Temuan utama mengungkapkan bahwa AI telah meningkatkan efisiensi pembelajaran dan akses terhadap sumber daya digital, tetapi masih mengalami keterbatasan dalam aspek interaksi manusiawi dan pemahaman konteks bahasa yang kompleks. Kesimpulan penelitian ini menegaskan bahwa optimalisasi AI dalam pendidikan bahasa Arab memerlukan pendekatan pedagogis yang lebih adaptif serta peningkatan literasi digital di kalangan pengguna. Studi ini berkontribusi dengan menawarkan wawasan mendalam tentang faktor-faktor yang memengaruhi adopsi AI serta memberikan rekomendasi strategis bagi pengembang teknologi dan pendidik guna menciptakan ekosistem pembelajaran yang lebih inovatif dan inklusif berbasis AI. Kata kunci: Adoption, Kecerdasan Buatan, Efektivitas, Pembelajaran Bahasa, Pedagogi